Model of Maternal and Child Health (MCH) Surveillance System on Women Workers to Save the First 1000 Days of Life - Putri Ayuni Alayyannur; Tri Martiana; Sho'im Hidayat; Normala Ibrahim (Universitas Airlangga, 2020)
Introduction: There are risk of physical, chemical, biological, ergonomic, and psychosocial hazards in workplace which may pose harm to women and their fetuses, especially if it is related to chemical hazards. Chemicals and radiation at workplace may increase the incidence of congenital anomalies, infant morbidity and mortality as well as recurrent abortion. The purpose of this study was to compile MCH surveillance. Method: A qualitative study design was used and a case study was conducted on three manufacturing companies in Sidoarjo District from August to October 2017. Thirty respondents from each company were selected using accidental sampling. Socio demographic and job-related data were obtained from the respondents. The variables of this research were personnel that were given training about public health center, data types, data instruments, data collection, data processing, data analysis, information dissemination, and comprehensive MCH information. Result: The MCH surveillance system for women workers in order to save the first 1000 days of life consisted of inputs, processes, and outputs. Inputs included worker factors, company factors, surveillance staff factors, data types and data instruments. The surveillance process consisted of several processes including data collection, data processing, data analysis, and information dissemination. Output in this service model was comprehensive maternal and child health information that can be applied in company. Conclusion: MCH surveillance model consists of input, process, and output. Every industry has unique characteristic which is not found in other type of industry.Keywords: child, health, maternal, surveillance